Micro‐instillation of fluorescein with an inoculation loop for ocular surface staining in dry eye syndrome. Issue 2 (25th October 2017) - Courrier, Emilie; Renault, Didier; Kaspi, Mathilde; Marcon, Agathe; Lambert, Victor; Garcin, Thibaud; Chiambaretta, Frederic; Garhofer, Gerhard; Thuret, Gilles; Gain, Philippe
Abstract: Purpose: To describe and validate the micro‐instillation of fluorescein on the ocular surface by a disposable calibrated inoculation loop to improve corneal and conjunctival staining quality. Methods: Accuracy and precision of the volume of 0.5% sodium fluorescein collected by a single use 1  μ l‐calibrated inoculation loop were measured using a precision balance. Twenty patients (40 eyes) suffering from dry eye syndrome were enrolled in a prospective interventional nonrandomized study. Fluorescein was instilled with the loop, and slit‐lamp images were taken within 30 seconds using cobalt blue light with and without a yellow barrier filter. For comparison, after a washout period, the same images were retaken after instillation of one drop of fluorescein from a single‐dose unit. The main outcome measure was the staining quality assessed by three experts, blind to the instillation method. Patient discomfort (tolerance, by a questionnaire) was also compared. Results: The mean volume collected by the loop was 1.18 ± 0.12  μ l, compared with 33.70 ± 6.10  μ l using the single‐dose unit. The loop avoided excess dye responsible for unpleasant tearing, masking of lesions and rapid diffusion into the stroma. Micro‐instillation greatly improved image quality without losing information. The yellow filter further improved image contrast. Tolerance was excellent. Conclusion: The 1  μ l‐calibrated inoculation loop is a safe, convenient, inexpensive, disposable, sterile, well‐tolerated tool for reproducible micro‐instillation of commercial fluorescein. By greatly improving staining quality, it will help standardize assessment of dry eye severity.